Unified operation monitoring and security warning platform based on big data in energy group - Jing WANG; Kunlun GAO; Chaoyi BIAN; Xiao LIANG (Dianxin kexue)
With the increasing of information assets of energy group,in order to effectively cope with information security risks,using the big data and the intersecting confirmation mechanics of multi-source data,a monitoring and security warning platform was designed for information devices and application systems in energy group.By the global analysis of big multi-source data,the real-time awareness of risk and situation could be achieved,which was valuable for the progress of operation and management level of information system and timely warning of the spread of information risk to the power system.